Model Layanan Pendidikan Inklusif di Indonesia - Jannah, Alfia Miftakhul; Setiyowati, Asih; Lathif, Khusna Haibati; Devi, Nina Deliana; Akhmad, Fandi (ANWARUL, 2021)
The government's high attention to the implementation of education in Indonesia is evidenced by the enactment of Law No. 20 of 2003 concerning the National Education system, namely equal distribution of education without discrimination against Children with Special Needs (ABK). However, the implementation of inclusive education in Indonesia has not run perfectly as the purpose of implementing inclusive education. Some schools appointed as implementing inclusive schools only run perfunctory. Although there are many inclusive schools in Indonesia, the quality of inclusive schools in Indonesia is still lacking. This study aims to analyze the inclusive education service model and its implementation in Indonesia, and the quality of inclusive schools in Indonesia. The research was conducted using a paper research method, namely reviewing and understanding studies related to the title. The results of this study showed that the model of education services and the implementation of inclusive education in Indonesia is still of low quality, this is because schools do not yet have readiness in implementing inclusive education.